Eribulin Provides a Remarkable Effect in Trabectedin-Resistant Myxoid Liposarcoma. (16th November 2020) - Tamiya, Hironari; Sabe, Hideaki; Yamashita, Katsunari; Imura, Yoshinori; Wakamatsu, Toru; Takenaka, Satoshi
Abstract : Adriamycin-based chemotherapy is commonly used for malignant soft tissue sarcoma including myxoid liposarcoma. However, in the case of unavailability or failure of the adriamycin-based regimen, trabectedin or eribulin can produce a good antitumor effect for myxoid liposarcoma. We relate the experience of a 64-year-old female with myxoid liposarcoma, who noticed a nodule on her left thigh and visited our institute. At initial presentation, the tumor was 18.7 cm in diameter, and the magnetic resonance imaging (MRI) showed a malignant lipomatous tumor with a myxoid component. We recommended that she undergo treatment; however, she refused. Three years later, the tumor had grown larger, so she finally decided to undergo treatment. A needle biopsy revealed a myxoid liposarcoma. The tumor massively involved the neurovascular structures; we thus determined that hip disarticulation was inevitable. Two years later, metastases in the right thigh, left lung, right ileum, and abdominal space were pointed out and chemotherapy was initiated. Adriamycin was unusable due to cardiac dysfunction, so trabectedin was administered; however, the tumors progressed. Eribulin was subsequently started and has been considerably effective for more than 2 years without severe adverse effects. In conclusion, we experienced a case showing the remarkable and long-lasting effect of eribulin against trabectedin-resistant myxoid liposarcoma.